Greenland's Arctic advantage: Articulations, acts and appearances of sovereignty games. (June 2020) - Jacobsen, Marc
Greenland representatives successfully use the renewed international geostrategic interest in the Arctic to enhance Greenland's foreign policy sovereignty. This is facilitated by Denmark's dependence on Greenland's geographic location and continuous membership of the Danish Realm for maintaining the status of an Arctic state, which recently has become one of the five most important security and foreign policy priorities. The dependency gives Greenland an 'Arctic advantage' in negotiations with Denmark, while turning circumpolar events into strategic arenas for sovereignty games in the aim to move the boundary of what Greenland may do internationally without Danish involvement. This article analyzes how these games unfold in the Arctic Council, at the high-level Ilulissat meetings and at circumpolar conferences where Greenland representatives articulate, act and appear more foreign policy sovereignty through outspoken discontent, tacit gestures and symbolic alterations. Altogether, this contributes to the expanding of Greenland's foreign policy room for maneuver within the current legal frameworks, while enhancing Greenland's international status and attracting external investments, important in their striving towards becoming a state with full formal Westphalian sovereignty.